Optimization of Vortex Tube Design Parameters Using the Taguchi Method - Himmet Erdi Tanürün; Adem Acır (Gazi Üniversitesi Fen Bilimleri Dergisi)
In this study, the optimization of a vortex tube (VT) with a fixed tube diameter and boundary conditions was attempted by determining four different design factors: the value of the conical valve degree (α), the number of nozzles (N), the cold flow exit diameter (Dcold exit), and the nozzle inlet diameter (Dnozzle), to improve the Cooling Coefficient of Performance (COPcooling). For each identified factor, five different levels were assigned, and an L25 orthogonal series was constructed using the Taguchi approach. The 3D-designed cases were subjected to numerical analysis in the ANSYS Fluent software program using the standard k-epsilon turbulence model. The effect levels of the design parameters were determined using the Analysis of variance (ANOVA) approach. Furthermore, after obtaining an empirical equation with COPcooling as the independent variable through Regression analysis, a confirmation test was conducted. The results indicated that the order of influence of the five parameters on COPcooling was N> Dnozzle> Dcold > α, with the N parameter having the strongest impact on the COPcooling in the VT, while the α parameter had the least effect. Additionally, the optimal VT showed a 40.3% improvement in COPcooling, when compared to a VT with initial geometric parameters. It has been identified that using the Taguchi approach for VT geometry optimization significantly enhanced performance